2018
DOI: 10.1016/j.schres.2017.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Impaired contextual fear-conditioning in MAM rodent model of schizophrenia

Abstract: The methylazoxymethanol acetate (MAM) rodent neurodevelopmental model of schizophrenia exhibits aberrant dopamine system activation attributed to hippocampal dysfunction. Context discrimination is a component of numerous behavioral and cognitive functions and relies on intact hippocampal processing. The present study explored context processing behaviors, along with dopamine system activation, during fear learning in the MAM model. Male offspring of dams treated with MAM (20mg/kg, i.p.) or saline on gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 95 publications
7
11
0
Order By: Relevance
“…Moreover, we demonstrated that MAM-treated rats have no alteration in contextual fear conditioning. A recent study from our group suggests that MAM-treated animals have a deficiency in context discrimination to predict a future aversive situation [29]. In the contextual fear conditioning experiment, we observed a similar expression of conditioned response between saline and MAMtreated animals.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, we demonstrated that MAM-treated rats have no alteration in contextual fear conditioning. A recent study from our group suggests that MAM-treated animals have a deficiency in context discrimination to predict a future aversive situation [29]. In the contextual fear conditioning experiment, we observed a similar expression of conditioned response between saline and MAMtreated animals.…”
Section: Discussionsupporting
confidence: 78%
“…In the SHR strain, the contextual fear conditioning deficit is specifically reversed by the administration of antipsychotic drugs ( Calzavara et al, 2009 ), being suggested as a model for the cognitive symptoms of schizophrenia. Contextual fear conditioning deficits are also seen in other animal models for schizophrenia ( Duffy et al, 2010 ; Gill et al, 2017 ; Latusz et al, 2017 ). Our findings therefore point to beneficial effects of CBD on the cognitive impairments and are in accordance with a recent work showing that prolonged treatment with CBD improves the deficits on recognition and working memory in the poly I:C model ( Osborne et al, 2017 ).…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, these animals show deficits in social behavior (Flagstad et al 2004;Le Pen et al 2006;Hazane et al 2009) equivalent to the negative symptoms, as well as in cognitive tasks, including impairments in spatial learning and memory (Gourevitch et al 2004;Hazane et al 2009;Ratajczak et al 2015;Gastambide et al 2015;Gill et al 2017), cognitive flexibility (Moore et al 2006) and problem-solving (Featherstone et al 2007). MAM-17 rats also have reduced thickness in cortical and subcortical regions (Moore et al 2006;Flagstad et al 2004;Featherstone et al 2007;Matricon et al 2010;Hradetzky et al 2012), dysregulated dopamine (DA) system (Grace 2017) and parvalbumin (PV) loss in ventral subicullum, HPC and PFC (Penschuck et al 2006;Lodge et al 2009;Gill & Grace 2014).…”
Section: Introductionmentioning
confidence: 99%